2002
DOI: 10.1016/s0304-405x(02)00152-6
|View full text |Cite
|
Sign up to set email alerts
|

Strategic IPO underpricing, information momentum, and lockup expiration selling

Abstract: Managers usually do not sell any of their own shares in an initial public offering but instead wait until the end of the lockup period. We develop a model in which managers strategically underprice IPOs in order to maximize personal wealth from selling shares at lockup expiration. First-day underpricing initiates information momentum-it attracts attention to the stock, thereby shifting the demand curve for the stock outwards. This allows managers to sell shares at the lockup expiration at prices higher than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(122 citation statements)
references
References 31 publications
9
110
2
1
Order By: Relevance
“…This goes against Hypothesis 5, which states that lock-in agreements and underpricing are substitute devices. Still, our finding is line with the fact that shareholders of heavily underpriced firms do not sell many shares in the IPO, but rather wait until the lock-in expiry (Aggarwal et al 2002). We also find that firms hiring a highquality underwriter have larger abnormal returns at the lock-in expiry, which does not support Hypothesis 6…”
Section: Resultscontrasting
confidence: 60%
“…This goes against Hypothesis 5, which states that lock-in agreements and underpricing are substitute devices. Still, our finding is line with the fact that shareholders of heavily underpriced firms do not sell many shares in the IPO, but rather wait until the lock-in expiry (Aggarwal et al 2002). We also find that firms hiring a highquality underwriter have larger abnormal returns at the lock-in expiry, which does not support Hypothesis 6…”
Section: Resultscontrasting
confidence: 60%
“…Developing this idea, Aggarwal, Krigman, and Womack (2002) argue that severe underpricing generates "information momentum," resulting in a higher market price at the end of the lockup period when insiders typically sell some of their shares. While this may be true, it is not clear that the benefits to the issuing firm exceed the opportunity cost associated with the increased dilution from underpricing the IPO.…”
Section: Alternative Explanations For the Underpricing Of Internementioning
confidence: 99%
“…As Chen and Ritter (2000) and Aggarwal, Krigman, and Womack (2002) argued, recommendations can boost share price, which is important for insiders wishing to sell their shares at the end of the lock-up period. Academic research has pointed out the importance of analyst coverage over the years.…”
Section: Can Analyst Coverage Reduce the Ipo Underperformance Phenomementioning
confidence: 99%
“…Their results show a clear link between the IPO method and analyst coverage. Rajan and Servaes (1997) and Aggarwal, Krigman, and Womack (2002) argued that underpricing attracts an analyst following. Bradley, Jordan, and Ritter (2003) and Corwin and Schultz (2005) found that having an underwriting syndicate is related to research coverage.…”
Section: Can Analyst Coverage Reduce the Ipo Underperformance Phenomementioning
confidence: 99%